Efektivitas Model Bertukar Pasangan dengan Pendekatan SETS (Sciense, Enviroment, Teknohlogy And Society) Terhadap Hasil Belajar Fisika - Jusriana, Andi; Ibrahim, Siska Peronika (Al-Khazini, 2021)
This study aims to find out: 1) the physics learningoutcomes of students in global warming learning which is taught by using the exchange pair model with the approach, 2) the physics learning outcomes of students in global warming learning that are taught using the conventional model, 3) whether the learning model is exchanging pairs with the SETS approach is effective on the learning outcomes of class VII students of SMP Negeri 1 Galesong Utara. The research method is a Quasi Experimental Design with a Posttest Only research design, Non-Equivalent Control Group Design. The population of all class VII students of SMP Negeri 1 Galesong in the 2018/2019 academic year consisted of 7 classes, the research sample consisted of 2 classes consisting of class VIIA as the experimental class and VIID as the control class. The results showed that the Physics learning outcomes of students who were taught with the pair exchange learning model with the SETS approach in class VII A SMP Negeri 1 Galesong Utara could be categorized in the high category, namely the average value of 82.14 and the learning model of exchanging pairs with the SETS approach was effective. towards improving the learning outcomes of class VII students of SMP Negeri 1 Galesong Utara